What does ‘adaptive programming’ mean in the health sector? - Tulloch, Olivia (ODI, 2015)
• There is considerable interest in the concept of adaptive developmen t and what it may look like in different sectors, including health. • Adaptive types of programming from the health sector are relatively ad vanced; as we work towards the Sustainable Development Goals (SDGs), e xperiences in health can provide useful lessons for other areas of dev elopment. • The international health community may not use the label ‘ adaptive development’, but many are already conducting adaptive work. ‘Quality improvement’ is one such tried and tested approach. • Quality improvement is problem-driven, iterative and flexible. The methodolog y and principles can be used to identify, test and implement changes i n any context or part of a health system. • Quality improvement is bei ng used successfully, but there is still limited experience and eviden ce of how to apply its values and philosophy beyond the project level and embed it within national structures and systems. • Systems thinkin g and analysis of the political economy environment may help embed com plex interventions like quality improvement and sustain their achievem ents